Value Chain Study of Karen Woven Textiles. The Case Study of Ban Sob Had Weaving Group. - Khuankaew, Chamroen; เนตรสว่าง, ณัฏฐรินดา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to analyze the value chain of Karen woven textiles produced by Ban Sob Had weaving group in Ban Luang Subdistrict, Chom Thong District, Chiang Mai Province. Using qualitative research methods, data was collected through interviews and focus groups with weavers and relevant agencies. The findings reveal that while raw materials are sourced, supplier networks remain underdeveloped. Production maintains traditional hand-weaving techniques and develops distinctive local patterns. For outbound logistics, a learning center serves as the main distribution point with postal delivery services. Marketing leverages cultural storytelling with value-based pricing, while service includes quality guarantees and product adjustments. Supporting activities show the group utilizes technology for customer communication, maintains a flexible organizational structure with a consignment system providing direct income to members, transfers knowledge across generations to develop weaving skills, and selects quality raw material suppliers while utilizing local resources. Key development opportunities include: establishing supplier and transportation networks, digitizing pattern documentation, developing packaging and branding that reflects community identity, creating sustainable financial strategies, and promoting technology training. These findings can be applied to enhance competitiveness and sustainability of indigenous textile handicraft groups in other contexts.